2000
DOI: 10.1016/s0092-8674(00)80827-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Transcription-Coupled Repair of 8-oxoGuanine

Abstract: Analysis of transcription-coupled repair (TCR) of oxidative lesions here reveals strand-specific removal of 8-oxo-guanine (8-oxoG) and thymine glycol both in normal human cells and xeroderma pigmentosum (XP) cells defective in nucleotide excision repair. In contrast, Cockayne syndrome (CS) cells including CS-B, XP-B/CS, XP-D/CS, and XP-G/CS not only lack TCR but cannot remove 8-oxoG in a transcribed sequence, despite its proficient repair when not transcribed. The XP-G/CS defect uniquely slows lesion removal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
86
1
4

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(98 citation statements)
references
References 0 publications
7
86
1
4
Order By: Relevance
“…Cells from CS patients are more sensitive than wild type cells to DNA damage induced by ultraviolet (UV) light (Wade and Chu, 1979), 4-Nitroquinoline-1-oxide (4NQO) (Wade and Chu, 1979), N-acetoxy-2-acetylaminofluorene (NA-AAF) (van Oosterwijk et al, 1996), ionizing radiation, and hydrogen peroxide (Cooper et al, 1997;Leadon and Cooper, 1993). CS cells are deficient in transcription coupled repair (TCR) of lesions caused by UV irradiation (Evans and Bohr, 1994;Venema et al, 1990) or oxidative stress (Cooper et al, 1997;Le Page et al, 2000). Furthermore, RNA synthesis recovers more slowly in UV-treated CS cells than in wild type cells .…”
Section: Introductionmentioning
confidence: 99%
“…Cells from CS patients are more sensitive than wild type cells to DNA damage induced by ultraviolet (UV) light (Wade and Chu, 1979), 4-Nitroquinoline-1-oxide (4NQO) (Wade and Chu, 1979), N-acetoxy-2-acetylaminofluorene (NA-AAF) (van Oosterwijk et al, 1996), ionizing radiation, and hydrogen peroxide (Cooper et al, 1997;Leadon and Cooper, 1993). CS cells are deficient in transcription coupled repair (TCR) of lesions caused by UV irradiation (Evans and Bohr, 1994;Venema et al, 1990) or oxidative stress (Cooper et al, 1997;Le Page et al, 2000). Furthermore, RNA synthesis recovers more slowly in UV-treated CS cells than in wild type cells .…”
Section: Introductionmentioning
confidence: 99%
“…Mismatch repair proteins may also help in the control of DNA oxidation levels (Leadon and Avrutskaya, 1997;DeWeese et al, 1998;Colussi et al, 2002). Transcription-coupled excision repair of 8oxoG guarantees the removal of the oxidized guanines from the transcribed strand of active genes (Le Page et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that CS cells are de®cient in the nucleotide excision repair (NER) pathway that removes ultraviolet light (UV) induced lesions from the transcribed strand of active genes (van Ho en et al, 1993;Venema et al, 1990). Defective transcription-coupled repair (TCR) in CS cells is not only observed after UV irradiation, but also after oxidative stress Le Page et al, 2000b). The clinical features of CS are di cult to reconcile with a repair de®ciency limited to TCR of UV-induced or bulky lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features of CS are di cult to reconcile with a repair de®ciency limited to TCR of UV-induced or bulky lesions. Consequently, it has been speculated that subtle defects in the repair of oxidative DNA lesions may contribute to the complex phenotype of a icted individuals Dianov et al, 1997Dianov et al, , 1999Le Page et al, 2000b;Nouspikel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation